Examining the Effects of Outpatient Services for Cleft Lip and Palate at the Heredity Clinic - NAKANII, Mihoko; YAMANOUCHI, Yasuko; INAGAWA, Kiichi; SHINOYAMA, Mika; MORIGUCHI, Takahiko; MIMURA, Kuniko; SATO, Yasumori (Journal of Japanese Cleft Palate Association, 2013)
In recent years, there has been an increased awareness of the need to incorporate assistance from heredity specialists to provide multidisciplinary team services for the treatment of cleft lip and palate. We conducted a semi-structured questionnaire survey involving 26 mothers of asymptomatic children with cleft lip and palate who visited the heredity clinic between October 2009 and December 2010 to examine the effects of outpatient services for cleft lip and palate, and consider future approaches. The survey results showed that these mothers were concerned about various issues related to heredity such as the future of their children (children with cleft lip and palate, and their brothers/sisters-to-be), the rate of recurrence in subsequent pregnancy, causes of recurrence, and preventive methods. However, 70% of them had not managed to talk to medical professionals about these issues for such reasons as not knowing the right person to ask. They considered it desirable that such information be provided at early stages, during pregnancy and immediately after birth. Regarding the effects of attendance at the heredity clinic, 24 mothers (92.3%) indicated that the outpatient services were “helpful” because it enabled them to: 1) obtain information on heredity (the recurrence rate and means of prevention); 2) obtain emotional support; 3) know where to ask for genetic information; and 4) organize information. The 24 mothers answered ‘yes’ when asked whether they would recommend and encourage others to visit the outpatient heredity clinic. In contrast, 2 mothers (7.7%) indicated that the outpatient services were “not helpful” because they could not obtain new information. This suggested the need to develop and implement appropriate means for heredity counseling and ongoing support. Based on these findings, we revised our leaflet describing the primary medical condition of cleft lip and palate to include information on heredity counseling and where to find it. We are currently providing a verbal explanation of the services using the leaflet. Recognizing that heredity-related issues are a sensitive subject, we exchange information with heredity specialists when necessary. We pay attention to the facial expressions and utterances of children with cleft lip/palate and their families during treatment phases to provide appropriate services. There is an increasing demand for support that takes into consideration the lives of patients’ families. It is desirable to develop collaboration between heredity specialists and psychologists to facilitate a multidisciplinary team approach to improving support in relation to heredity.